Acquired megaoesophagus in a Suffolk ram. Issue 2 (25th November 2016) - Laurence, Michael; Curnow, Megan; Blignaut, Dawie
Abstract : A one‐year‐old Suffolk ram was evaluated after a four‐month history of intermittent left‐sided bloating and regurgitation. The ram had been slowly losing condition while other sheep in the cohort were gaining weight. Severe megaoesophagus was confirmed on lateral thoracic and neck radiographs and a firm, 6‐cm mass at the oesophageal sphincter was palpated during standing exploratory laparotomy. Postmortem examination confirmed an abscess was the cause of the partial oesophageal obstruction. The abscess yielded pure light growth of Streptococcus alactolyticus, an organism not reported to be associated with infection in sheep. Intermittent bloating is an unusual presentation in ruminants, and acquired megaoesophagus has been reported only very occasionally in sheep. This case report expands the list of differential diagnoses for abnormal regurgitation and intermittent bloating, and provides another specific cause of obstructive gastrointestinal disease in sheep. Acquired megaoesophagus was an unusual sequela of this primary disease.